L'action d'intérêt collectif - Verge, Pierre (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
Group action is inherent to a pluralistic society. In various fields, numerous bodies purport to defend and promote the common interest of their members which is also the raison d'être of the group. How receptive is the judicial system to attempts by such groups to legally defend the common aim ? « Collective actions » are brought to assure the legal protection of a collective value which is not of a general societal nature as is the public interest. However, their purpose is not to defend the subjective patrimonial interest of the members of the group or even of the group itself. The underlying collective interest is first to be objectively identified in order not to unduly curtail the reception of the collective action; then it is for the Court to establish whether there is a sufficient relationship between the collective interest and the general objects of the group, as officially defined, in order to allow the latter to act. This analysis of the « sufficient interest », as required by Sec. 55 C.C.P., it is suggested, appears to be more adapted to the nature of the collective action than the immediate requirement of a « direct and personal » interest from the group, at least if this notion is to be understood as involving some form of patrimonial interest, as in most trials.